Electrochemical Dynamics of a Single Platinum Nanoparticle Collision Event for the Hydrogen Evolution Reaction - Xiang, Zhi-peng; Deng, Hai-qiang; Peljo, Pekka; Fu, Zhi-yong; Wang, Su-li; Mandler, Daniel; Sun, Gong-quan; Liang, Zhen-xing (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2018)
Chronoamperometry was used to study the dynamics of Pt nanoparticle (NP) collision with an inert ultramicroelectrode via electrocatalytic amplification (ECA) in the hydrogen evolution reaction. ECA and dynamic light scattering (DLS) results reveal that the NP colloid remains stable only at low proton concentrations (1.0mm) under a helium (He) atmosphere, ensuring that the collision events occur at genuinely single NP level. Amperometry of single NP collisions under a He atmosphere shows that each discrete current profile of the collision event evolves from spike to staircase at more negative potentials, while a staircase response is observed at all of the applied potentials under hydrogen-containing atmospheres. The particle size distribution estimated from the diffusion-controlled current in He agrees well with electron microscopy and DLS observations. These results shed light on the interfacial dynamics of the single nanoparticle collision electrochemistry.